ANTIBACTERIAL ACTIVITY OF PAKISTANI RHAZYA STRICTA - Ahmad, Shahnaz; Fatima, Kaneez; Rahman, Atiq-ur- (Biological Sciences - PJSIR, 2004)
The crude ethanolic extract of Rhazya stricta Dcne; (Family, Apocynaceae) was tested, on the basis of medicinal and folklore reports for antimicrobial activity against a wide range of gram - positive and gram - negative organisms. Leaves extract was found to be more active as compared to other parts exhibiting 69.23% and 66.66% activity against gram - positive and gram - negative organisms respectively. Seeds extract exhibited maximum inhibitory activity (“A” category zone) i.e. 23.07% and 16.66% against gram - positive and gram - negative organisms respectively as compared to other parts of Rhazya stricta. Reference standard i.e. co-trimoxazole exhibited only 7.69% “A” category zones against gram - positive organisms only.